ANALISIS SUMBER DAN PENGGUNAAN KAS PADA PT. BANK TABUNGAN NEGARA (PERSERO) Tbk - Lastri Sitanggang; Helprida Simamora (Jurnal PROFITA : Akuntansi dan Manajemen, 2022)
This research entitled “Sources and Allocation of Cash Analysis at PT. Bank Tabungan Negara (Persero) Tbk". The purpose of this study was to analyze the sources and allocation of cash and what factors influence changes in cash at PT. Bank Tabungan Negara (Persero) Tbk in period 2016 to 2019. Data used in this study are secondary data with documentation techniques obtained from the (Otoritas Jasa Keuangan) OJK website. Population of research is data from the company’s financial position repost and the sample of this research is the data from company’s financial position report for the period 2016-2019. The data analysis technique used is horizontal analysis. The results of this study indicate that the sources and allocation of cash for each period has a change which is an increase in cash for each other. there was a difference in each period of the sources and allocation of cash either increase. The main factors that effect the cah changes were Time deposits, Placements with Bank Indonesia and Kredits.